2012
DOI: 10.1590/s1678-77572012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion of nanofilled and microhybrid composite resins photo-activated by different generations of LEDs

Abstract: Objective This study aimed at evaluating the degree of conversion (DC) of four composite resins, being one nanofilled and 3 microhybrid resins, photo-activated with second- and third-generation light-emitting diodes (LEDs). Material and methods FiltekTM Z350 nanofilled composite resins and Amelogen® Plus, Vit-l-escenceTM and Opallis microhybrid resins were photo-activated with two second-generation LEDs (Radii-cal and Elipar Free LightTM 2) and one third-generation LED (Ultra-Lume LED 5) by continuous light mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 24 publications
2
28
0
4
Order By: Relevance
“…According to many previous studies, several Bis-GMA based resin composite materials exhibited considerable unreacted monomers in the final restorations, with a degree of conversion were in the range of 52e75% with most of the materials were in the range of 55e60%, under conventional irradiation methods [6,15,16,18]. The minimum DC% for clinically acceptable restoration has not yet been exactly recognized [6].…”
Section: Discussionmentioning
confidence: 99%
“…According to many previous studies, several Bis-GMA based resin composite materials exhibited considerable unreacted monomers in the final restorations, with a degree of conversion were in the range of 52e75% with most of the materials were in the range of 55e60%, under conventional irradiation methods [6,15,16,18]. The minimum DC% for clinically acceptable restoration has not yet been exactly recognized [6].…”
Section: Discussionmentioning
confidence: 99%
“…Composite resins often do not polymerize completely when using light, and short-chain polymers may remain un-bonded, albeit in small quantities (9,10). It has been suggested that there is a significant relationship between leaking, non-polymerized monomers from composite resins and cytotoxic effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…Variações, mesmo que pequenas, na composição do material são suficientes para alterar o índice de refração durante a fotoativação. Tipo, quantidade, tamanho e formato das partículas de carga, bem como a própria silanização das mesmas, podem modificar o índice de refração, levando a maior dispersão da luz e comprometer a transmissão da luz pelo corpo do material 3,17,29 . É importante ressaltar que a transmissão da luz diminui de modo exponencial com o aumento da espessura 3 .…”
Section: Discussionunclassified
“…Vale ressaltar que uma polimerização inadequada pode afetar as propriedades físicas, mecânicas e biológicas do material, levando ao insucesso clínico, caracterizado pelo aumento da microinfiltração marginal, diminuição da microdureza e da estabilidade de cor, causando manchamento na restauração, bem como um aumento na quantidade de monômeros residuais, responsáveis por eventuais danos ao tecido pulpar, além de sensibilidade pós-operatória [6][7][8][9][10] . Diversos trabalhos na literatura demonstram a profundidade de polimerização de resinas compostas 6,8,9,11 , contudo o valor de atenuação da luz não é claramente definido em diferentes espessuras do material.…”
Section: Introductionunclassified